Kadar Air dan Vitamin C pada Proses Pembuatan Tepung Cabai (Capsium annuum L) - Nico Syahputra Sebayang (Universitas Islam Negeri Ar-Raniry, 2016)
This study was conducted to determine the level of water and Vitamin C in the process of making chilli flour. The research used randomized completely design (RCD) with two factors, drying temperature (50 ° C , 60 ° C , 70 ° C , 80 ° C) and long drying (12 hours , 14 hours , 16 hours , 18 hours) , The results showed that the drying temperature had highly significant effect on the level of water and vitamin C; Long drying had a highly significant effect on the level of water and vitamin C; and the interaction of temperature and length of drying showed a significant different influence on the level of water and vitamin C.